Лялька і обряд - Пешикан-Люштанович, Л. (Народна творчість та етнологія, 2012)
The first part of this article is devoted to different forms of ritual folklore and the use of a doll in the traditional culture of the Balkan Slavs. Together with a doll which was used in the funeral rituals as a substitute for the third dead, if a family lost more than one its member (a doll was hidden in the ground), and the dolls which are used in the ceremonies in order to attract the rain or the harvest, we also look at the masks in the harvest rites. Those masks are considered to be alive dolls at the hands of the person who puts the mask on. The dead wolf is also considered to be a doll (vuchyna), if he is brought by the hunters, who are on his behalf asking for money and food as the price for future protection. The second part of the article analyzes how this ritual practice of the 19th – first half of the 20th century is reflected in contemporary Serbian theatre and particularly in the puppet play «The Myths of the Balkans» (by Slavolyub Stankovych), which received many awards. У првом делу рад се бави различитим формама обредног коришћења лутке у традиционалној култури балканских Словена. Поред лутке, која се користи у погребним обредима, као ритуална замена за трећег мртваца, када у истој породици умру два члана за редом (потрећавање), и лутке која се сахрањује / ископава да би изазвала / спречила кишу, предмет испитивања су поједине маске у обредима плодности које се препознају као лутка коју оживљава онај ко ставља маску на себе (оале, додоле). Као лутка разматра се и мртви вук, вучина, којега ловци носе и у његово име траже дарове у новцу и храни као цену за будућу заштиту.
Други део рада показује како се ова обредна пракса из 19, па и прве половине 20. века рефлектује у модерном српском театру у вишеструко награђиваној луткарској представи Славољуба Станковића «Митови Балкана».